Transcutaneous bilirubin monitoring predicts unexplained late-onset hemolysis in a very low birthweight infant. (December 2016) - Nagasaka, Miwako; Kikuma, Tomoe; Iwatani, Sota; Kurokawa, Daisuke; Yamana, Keiji; Maeyama, Kaori; Koda, Tsubasa; Matsumoto, Hisayuki; Taniguchi-Ikeda, Mariko; Iijima, Kazumoto; Nakamura, Hajime; Morioka, Ichiro
Abstract Background In term infants, transcutaneous bilirubin (TcB) monitoring can be used to predict hemolytic hyperbilirubinemia. However, it is not clear whether the technique can also be used to predict unexplained late-onset hemolysis in very low birthweight (VLBW) infants. Case presentation The case was an infant with a birthweight of 1154 g who developed unexplained late-onset hemolysis at 8 days of age. The hyperbilirubinemia rapidly worsened, and therefore both phototherapy and exchange transfusion were performed. TcB levels were measured using the JM-105 jaundice meter and found to have increased by >3 mg/dL since before the onset, demonstrating for the first time that the device clearly detects changes in hemolytic rate. Conclusions Although TcB levels did not correspond directly with total serum bilirubin levels in VLBW infants, the two values exhibited parallel changes in this case. Therefore, serial TcB monitoring may be useful in the early prediction of unexplained late-onset hemolysis in VLBW infants.